Antecedents of Entrepreneurial Intent: A Cross-Country Comparison of Generation Y University Students - Marire, Esther; Dhurup, Manilall (Journal of Reviews on Global Economics, 2018)
This paper convey the findings of a study carried out to compare the antecedents of entrepreneurial intentions of students from two universities within the Southern African continent. A cross-sectional survey, based on 400 students from two universities of two different countries (South Africa and Zimbabwe) was conducted using a self-administered questionnaire. Using the theory of planned behavior, personal attitude, subjective norms and perceived behavioral control, and entrepreneurial education were used to predict entrepreneurial intentions. Personal attitude and subjective norms and entrepreneurial education seem to positively influence behavioral intentions. Behavioral control showed insignificant predictive relationship with behavioral intentions. It is recommended that entrepreneurial education should be made a core and integral component of study at universities so that universities as social institutions can create an impetus with a holistic approach including all role players with adequate resources to support students in entrepreneurial ventures.